Investigating the Selective Control of Photoassociation of Yb2. (6th September 2021) - Cheng, Junxia; Tian, Bo; Li, Siyu; Wang, Jia; Wu, Shenjiang
Abstract : The selective control of photoassociation of Yb2 is investigated in theory. Based on ab initio to rationalize Franck–Condon filtering, the optimal target states of photoassociation have been obtained. The corresponding vibrational transitions from X 1 Σ + g to the excited state (A 1 Σu +, B 1 Πu, C 1 Σu +, and D 1 Πu ) are v ′ = 23, 50, 55, and 0, respectively. By using quantum wave packet dynamic methods, we calculated the yields with time evaluation for the selected target states. The projections of time-dependent wave functions of initial states on the target vibrational eigenstates reflected the synthetic yields of Yb2 . For target A 1 Σu +, we used Gaussian pulse to make the yield of v ′ = 23 up to 97% at 725 fs. After a laser pulse, the positive chirp promoted the yield of vibrational states to increase, but the negative chirp inhibited its decrease. For the D 1 Πu state, when laser intensity is 1.0 × 10 14 W/cm 2, the purity and yield of target state v ′ = 0 reached the maximum at 1350 fs. That is to say, changing the laser parameters and pulse shapes could control the photochemical reaction along our desired direction. These conditions will provide an important reference and suggest a scheme for a feasible photoassociation of further experimental and theoretical research studies. Current study may promote an important step toward the realization of highly accurate quantum manipulation and material synthesis.